(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims to determine and analyze the magnitude of the leader of Village Head Competence to the Success of Village Development in Ranolambot Village. The method that writer use in this research is quantitative method, is research method based on philosophy of positivism, used for researcher on population or sample . The sampling technique used is a simple random sampling technique from research in Ranolambot Village of 55 people. Data analysis techniques used are simple linear regression analysis and simple correlation analysis Based on the analysis of Correlation Coefficient (r) = 0.812 while the coefficient of determination (rÂ²) = 0.659. The result shows that the coefficient of determination is 65,9%. With these results can be explained that the increase of Village Development Success in by Village Head Competency of 65.9% while 34.1% is determined by other factors. Based on the results of the above research, the hypothesis put forward can be accepted that there is a degree of linkage and determination of power between the Village Head’s Competence to the Successful Village Development in Ranolambot Village. Based on the results of significant tests obtained Fcount = 102.542 at a significant level of 0.05 with degrees of freedom (df) = n - 2 = 53, then Ftabel 4.02. From the dat it is obtained that Fcount is greater than Ftable where Fcount 102.542> 4.02. Then Ha accepted and H0 rejected. This proves that there is a significant amount of influence between the Village Head’s Competence on the Success of Village Development in Ranolambot Village. Keywords: Village Head Competency, Successful Village Development